Simple Analytical Method on the Determination of Dexamethasone in Herbal Medicine - Pratiwi, Rimadani; Rahmawaty, Adira; Hasanah, Aliya Nur (Journal of Spectroscopy, 2022)
Chemical drugs have been added to some of the traditional herbal medicine to enhance the therapeutic effect. One of them is dexamethasone which is added in herbal pain relief. To determine the content of dexamethasone in herbal medicine, a quantitative analytical method was developed with the reaction of the formation of a dexamethasone-hydroxylamine complex with fluoranil which was measured by UV-Vis spectrophotometry. Under optimized conditions, the performance of this system to analyze dexamethasone exhibited a good analytical response. The correlation coefficient was (R2) of 0.9965 from a concentration of 1–40 g/mL, LOD, and LOQ of 0.21 μg/mL and 0.64 μg/mL, % recovery for concentrations of 80%,100%, and 120%, are 100.14% ± 0.58; 98.35% ± 1.19; and 99.00% ± 1.18, respectively; and %RSD is 0.75%. The sixteen herbal medicine samples were analyzed to confirm the application of this method. The result showed six samples confirmed containing dexamethasone with levels ranging from 7.44 to 21.61 μg/mL and confirmed with HPLC data. The UV-Vis spectrophotometry method is simple and effective for dexamethasone analysis in herbal medicine.